The Impact of Enrollment in an OER Course on Student Learning Outcomes - Grewe, Kim E.; Davis, William Preston (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Open Educational Resources (OER) are gaining acceptance as legitimate and effective teaching materials in higher education, particularly in 2-year institutions. Despite the steady growth in the availability and use of OER, there have been relatively few studies on the efficacy of OER and student achievement. This study analyzed the effect enrollment in an OER course had on student academic achievement when controlling for prior academic achievement in an introductory online history course at a large community college. Correlation analysis and simple linear regression were conducted. The results of this research indicate a significant positive moderate correlation between OER and student achievement. The study provided a process by which future, more rigorous efficacy studies can be conducted.